Nigeria : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that real GDP growth in Nigeria accelerated in 2003 on account of sharply higher oil and gas production and continued robust growth in the non-oil economy. Owing to favorable terms-of-trade developments, the external current account deficit narrowed sharply. This, however, masks rising non-oil import pressures and a widening non-oil external current account deficit. Macroeconomic conditions have improved considerably since late 2003, owing largely to fiscal prudence. The fiscal restraint that began in the last quarter of 2003 continued in the first half of 2004.